Intercultural Competency Needs For The Third Sector Professionals. - García-Aguilera, Francisco José; Fausto Lizaola, Celia; Vázquez Moreno, Elena (European Proceedings, 2019)
The Incheon Declaration, approved by UNESCO in 2015, plays a key role in the international context, by collecting recommendations and progress in the inclusive and intercultural education. The organizations that contribute in the educational field, are participating by accomplishing the Incheon Declaration goals. By taking the normative references as starting point, the role of NGOs, foundations, associations and religious organizations contribute to the socio-educational needs of every person. The aim of this research is to go deep into the training needs of professionals working in social organizations, due to their key role in the intercultural competency recognition as the main strategy to empower people and groups coming from increasingly diverse contexts. This research is a descriptive study and an analysis of the intercultural competency needs, skills and abilities in the third sector and its professionals. The methodology is based in a customized survey, filled by 80 professionals from the third sector. The results are a fundamental contribution to the diagnose of professionals’ educational needs, who work in diverse contexts and demand intercultural training.
Keywords: Educación inclusiva; Educación intercultural; Economía social; Inclusive education; Interculturality professionals; Social organizations; Third sector; Training needs